Increased Serum Pigment Epithelium-Derived Factor in Women with Gestational Diabetes Is Associated with Type 2 Diabetes - Tong-Huan Li; Chun-Jian Qiu; Xiao-Juan Yu; Dan-Dan Liu; Peng-Fei Zhou; Liang Wu (International Journal of Endocrinology)
Background. Pigment epithelium-derived factor (PEDF) is demonstrated to be elevated in diabetes patients. However, no reports have emerged in pregnant women with gestational diabetes mellitus (GDM). This study was undertaken to investigate serum PEDF levels in GDM women and to evaluate PEDF as a biomarker to predict diabetes postpartum. Methods. Serum PEDF concentration and clinical characteristics were detected in the pregnant women with GDM (n = 120) and without GDM (control group, n = 120). Results. PEDF levels were elevated in subjects with GDM versus controls. Univariate correlations showed that serum PEDF levels were positively correlated with fasting glucose and fasting insulin levels, respectively, and negatively correlated with adiponectin. Receiver operating characteristic (ROC) analysis demonstrated that the AUC of serum PEDF for diabetes mellitus in women postpartum was 0.893. Conclusion. Serum PEDF was elevated in pregnant women with GDM, which is probably an early detection marker for predicting development of GDM to diabetes mellitus.